Material-economic aspects of wooden pole fence-buildings: Examples from a flexible building method - Svantesson, Björn (FormAkademisk, 2023)
This paper examines different aspects of wooden pole fence-buildings through two different perspectives. In the first part of the article, the material-economic conditions and the nature of the crafts involved in the building technique is examined through a sloyd-theoretical perspective. By comparing approaches and methods of the wooden pole fence building-technique with those of domestic sloyd rather than architecture, an attempt is made at understanding the techniques epistemological nature. The versatile nature of the building technique is emphasized, and its regenerative qualities highlighted. The second part takes a closer look at the craft procedures involved in the making of a wooden pole fence-building through a processual reconstruction of a small barn based on a filmed documentation of the building process from the 1930s. Through practical experiments, attempts are made to understand and recreate the craft procedures documented in the film. Questions about the selection of wood for the barn and how material conditions affect the craft procedures are discussed. A filmed documentation of three of the procedures of the reconstruction gives an insight into the process.